METTL3 promotes drug resistance to oxaliplatin in gastric cancer cells through DNA repair pathway - Wang, Yi; Hong, Zhongshi; Song, Jintian; Zhong, Peilin; Lin, Liang (Frontiers in Pharmacology, 2023)
Gastric cancer (GC) poses a significant threat to human health and remains a prevalent form of cancer. Despite clinical treatments, the prognosis for GC patients is still unsatisfactory, largely due to the development of multidrug resistance. Oxaliplatin (OXA), a second-generation platinum drug, is commonly recommended for adjuvant and palliative chemotherapy in GC; however, the underlying mechanisms of acquired resistance to OXA in GC patients are not yet fully understood.In this study, we aimed to explore the potential mechanisms of OXA resistance in GC by employing bioinformatics analysis and conducting in vitro experiments. Specifically, we focused on investigating the role of methyltransferase-like 3 (METTL3). Our findings revealed that the knockdown of METTL3 significantly impeded the proliferation and migration of GC cells. METTL3 knockdown induced apoptosis in OXA-resistant GC cells and enhanced their sensitivity to OXA. Furthermore, we found that DNA repair pathways were significantly activated in OXA-resistant GC cells, and METTL3 knockdown significantly inhibited DNA repair pathways. Another important finding is that METTL3 knockdown and OXA-induced GC cell death are additive, and the targeted METTL3 can assist OXA treatment. Collectively, our findings suggest that METTL3 knockdown can augment the sensitivity of GC cells to OXA by impeding DNA repair processes. Consequently, targeting METTL3 holds great promise as a viable adjuvant strategy in the treatment of GC patients.